Non-formal civic education in Spain: a social cartography approach - López-Meseguer, Rafael; Gutiérrez Sánchez, Marta; Pedreño Plana, Marina; Gómez-Núñez, María Isabel (Education, Citizenship and Social Justice, 2025)
The work of non-governmental organizations in promoting citizenship competencies is one of the most effective forms of civic education today. Nonetheless, it has not received much attention from academia. This present research, using the method of social cartography and qualitative content analysis, analyzes the non-formal civic education work carried out by 156 non-governmental organizations in Spain. The results give an overview of the scope, target audience, types of activities, and topics that these organizations address, providing some significant examples. Additionally, the research includes an analysis of the institutional context in which these organizations operate based on 10 in-depth interviews. Finally, the findings point to the need to further focus on this type of education, integrate it into educational systems, and provide these non-governmental organizations with adequate resources to effectively carry out their work.
Keywords: civic education; social cartography; citizenship; non-formal education; non-governmental organizations (NGOs); spanish population